PEMIKIRAN DELIAR NOER MENGENAI GERAKAN ISLAM MODERN INDONESIA 1900-1942 - Iskandar, Irpan; Firdaus, Dede Wahyu (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2020)
Deliar Noer is Indonesian scholar in the field of Islamic politics and history in 20th century. His thoughts on the modern Indonesian Islamic movement 1900-1942 have made scientific contributions and become a reference for Islamic studies in Indonesia. The writing of this article aims to analyze the thoughts of a Deliar Noer in his book entitled